Review Paper : Wheat rusts in India: Resistance breeding and gene deployment - A review - Tomar, S. M. S.; Singh, Sanjay K; Sivasamy, M.; Vinod, 1 (The Indian Journal of Genetics and Plant Breeding, 2017)
This review paper presents the history of rust resistance breeding and deployment of resistant cultivars in different geographical areas of India. Much has been accomplished in controlling the wheat rusts through deploying resistant cultivars carrying diverse resistance genes in India. The genetic diversification in wheat has not only proved critical in developing resistant cultivars but also in the understanding of disease epidemiology and its dynamics and has gradually reduced the magnitude and frequency of epidemics. The gene Lr26 in combination with Lr13, Lr23 and Lr34 and the Agropyron segment carrying Lr24/Sr24 have played a crucial role in providing durable resistnace and protecting wheat from any epidemic threat to stable wheat production. In recent years, wheat has achieved relatively higher production stability as compared to other cereal crops by adopting strategic gene deployment. Only marginal increase in wheat area is recorded but the strategic deployment of rust resistance genes is most protective of crop production and crucial in sustaining the production levels.